The health and outlook of printing industry post-Covid-19: the insight into Malaysia printing industry - Masod, Muhammad Yusuf; Zakaria, Siti Farhana (Journal of Print and Media Technology Research, 2023)
While it is widely assumed that the printing industry is in a state of declining demand, or “sunsetting” worldwide, our study suggests that the printing industry in Malaysia shows a stabilizing trend. Print service providers (PSPs) diversify and exploit the trend for digitization and automation and also explore new market segments to stay relevant. The industry’s performance before, during, and after the pandemic from 2019 to Q2 2022 was analyzed. An interview with the top management of PSPs was conducted to obtain views on the impact of Covid-19 on the print business. The findings show macroeconomic factors’ are heavily influenced by growth and suggest that demand will remain resilient going forward, making the outlook for the printing industry optimistic despite domestic and global uncer- tainty. We also discovered that the pandemic has given PSPs a chance to reevaluate their operations and rebuild using technology to support their businesses in the post-Covid-19.